2017
DOI: 10.1007/978-3-319-58741-7_21
|View full text |Cite
|
Sign up to set email alerts
|

New Bounds on the Strength of Some Restrictions of Hindman’s Theorem

Abstract: The relations between (restrictions of) Hindman's Finite Sums Theorem and (variants of) Ramsey's Theorem give rise to long-standing open problems in combinatorics, computability theory and proof theory. We present some results motivated by these open problems. In particular we investigate the restriction of the Finite Sums Theorem to sums of at most two elements, which is the subject of a long-standing open question by Hindman, Leader and Strauss. We show that this restriction has the same proof-theoretic and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…Dzhafarov, Jockusch, Solomon, and Westrick [5] showed that HT 3 3 implies ACA 0 over RCA 0 . Carlucci, Ko lodzieczyk, Lepore, and Zdanowski [3] did the same for HT 2 4 . These principles are also complex in a more heuristic sense: There is no known way to prove even HT 2 2 other than to give a proof of the full HT, which has led Hindman, Leader, and Strauss [7] to ask whether every proof of HT 2 is also a proof of HT.…”
mentioning
confidence: 71%
See 2 more Smart Citations
“…Dzhafarov, Jockusch, Solomon, and Westrick [5] showed that HT 3 3 implies ACA 0 over RCA 0 . Carlucci, Ko lodzieczyk, Lepore, and Zdanowski [3] did the same for HT 2 4 . These principles are also complex in a more heuristic sense: There is no known way to prove even HT 2 2 other than to give a proof of the full HT, which has led Hindman, Leader, and Strauss [7] to ask whether every proof of HT 2 is also a proof of HT.…”
mentioning
confidence: 71%
“…One might hope to show, for instance, that there is a boundary between principles that "behave like HT", e.g. HT 2 4 , which as mentioned in the introduction was shown to imply ACA 0 in [3]; and those that "behave like versions of TS / RT", e.g. the thin version of HT 2 4 , which can easily be shown to follow from RT 2 4,2 .…”
Section: Open Questionsmentioning
confidence: 96%
See 1 more Smart Citation
“…(1) For every positive integers k, ℓ, RCA 0 ⊢ HT ≤3 3 → RT k ℓ (Dzhafarov et al [7]), (2) For every positive integers k, ℓ, RCA 0 ⊢ HT ≤2 4 → RT k ℓ (Carlucci et al [4]), (3) For every positive integers k, ℓ, RCA 0 ⊢ HT =3 2 with apartness → RT k ℓ (Carlucci et al [4]), (4) IPT 2 2 ≤ sc HT ≤2 4 (Carlucci [3]), (5) IPT 2 2 ≤ sc HT =2 2 with apartness (Carlucci et al [4]). Despite points (1) and (2), I have not been able to lift the combinatorial reductions in points ( 3) and ( 4) to exponents higher than 2.…”
Section: Nies: Shannon-mcmillan-breiman Theorem and Its Non-classical...mentioning
confidence: 99%
“…2 ) is unprovable in RCA 0 . The first author in joint work with Ko lodziejczyk, Lepore and Zdanowski later showed that HT ≤2 4 implies ACA 0 and that HT ≤2 2 is unprovable in WKL 0 [4]. However, no upper bounds other than those known for the full Hindman's Theorem are known for HT ≤2 k , let alone HT ≤3 k , for any k > 1.…”
Section: Introductionmentioning
confidence: 99%